Parents' perception of health care services for girls with Rett syndrome. (3rd April 2019) - Rodocanachi Roidi, Marina Luisa; Grange, Francesca; Cozzi, Francesca; Pari, Elisa; Toshimori, Kumiko; Ripamonti, Enrico
Abstract: Background: Rett syndrome (RTT) is a severe neurodevelopmental disorder, implying impairment and disability across several domains. Method: We investigated parents' perception of the caregiving process in a sample of 55 mothers and fathers of girls with RTT using the MPOC‐20 questionnaire. The association of parents' satisfaction with clinical variables has also been explored. Results: We obtained intermediate levels of satisfaction on the MPOC‐20 Coordinated and Comprehensive Care and Respectful and Supportive Care scales. The performance was lower on the scales Providing General Information and Providing Specific Information. Mothers' assessment was not associated with clinical variables such as walking disability, presence of scoliosis, or epilepsy. For children with greater degree of walking impairment, fathers expressed the need of having more information available. Conclusions: Although parents seemed satisfied of the caregiving process, clinicians should put more emphasis on their need of receiving general and specific information on RTT along the entire rehabilitation program.